Experiential Placements in Pharmacy : Quality Indicators for Best Practice Approaches to Experiential Placements in Pharmacy Programs. - Owen, Susanne; Stupans, Ieva (Carrick Institute for Learning and Teaching in Higher Education, 2008)
Final report from a study that was designed to identify and document good practice for experiential learning and teaching in Australian pharmacy programs to inform curriculum development across the health sciences. It found that experiential placements are regarded as an important part of the pharmacy course by all stakeholders, and are significant in developing skills, knowledge and attributes in the workplace. Key influences on experiential pharmacy placement are the eight functional areas of the Pharmaceutical Society of Australia competencies, linked to registration accreditation requirements and university-specific graduate attributes. A wide range of structural models and protocols exist within and across university courses, and planning is needed across the university sector to ensure improvement of quality. The study reveals good practice models for student reflections and communication, but notes a need for further development: in particular, the urgent need for recruitment, retention, and training of preceptors given pressures arising from increased student numbers. The study recommends a national depository of experiential placement learning and teaching assessment tasks; standardised developmental descriptors related to competencies as applicable to students at novice and advanced beginner stages; and further collaborative work with stakeholders to identify success indicators for preceptors, students, universities, sites and environments.